A new type of sternal gland present in Oxaea flavescens (Hymenoptera, Oxaeinae): Location and histology - Guerino, A. C. [UNESP]; Cruz-Landim, C. [UNESP] (My University, 1999)
The sternal glands of the abdomen of Oxaea flavescens consist of class III glandular cells, with the excretory canaliculus linking to the lateral intersegmental membrane of segments III, IV and V. The intersegmental membrane is augmented and folded into several lobes forming a reservoir covered by secretory cells. The intersegmental membrane is then transformed into an intima that lines a reservoir space containing secretions of a type of mucus which is periodic acid-Schiff positive. The storage of a great amount of secretion suggests that it is not used continuously. These glands are absent from males, indicating that their products must have a specific function linked to the female sex.
Keywords: Exocrine glands; Solitary Oxaea flavescens; Sternal glands; Tegumentary glands